Cleaner Production Strategy As A Supporting Analysis of Environmental Impact on Drinking Water Treatment Process Using Life Cycle Assessment Approach - Aulia Ulfah Farahdiba; Geafiata Amalia Nurbaiti; Tuhu Agung Rachmanto (Future Science)
The Drinking Water Treatment Plant has an impact on the environment due to its production process. This emerging impact can be studied strategically by carrying out the concept of cleaner production. Cleaner production is an integrated environmental management effort in a series of product life cycles. The output of this concept is to provide alternative management that is environmentally friendly. The principle of cleaner production is in line with the Life Cycle Assessment. This study examines data on drinking water treatment plants to provide certainty before being analyzed using Life Cycle Assessment (LCA). LCA is an approach method that can be used to identify and analyze environmental impacts resulting from all stages of the product life cycle to know which parts have the greatest impact on the environment.